The Legislative Authority of the House of Representatives (DPR) in Law-Making under the 1945 Constitution of the Republic of Indonesia - Zuhri, Basrial; Yandi, Rus; Zahmi, April; Triawan, Ade (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The amendments to the 1945 Constitution of the Republic of Indonesia post-reform have brought fundamental implications for the configuration of legislative authority within Indonesia’s constitutional system. One significant change is the strengthening of the authority of the People's Representative Council (DPR) as the holder of the power to make laws, as emphasized in Article 20, paragraph (1) of the 1945 Constitution. This article aims to comprehensively examine the legislative authority of the DPR in the lawmaking process according to the 1945 Constitution, as well as its implementation in Law Number 12 of 2011 on the Formation of Legislation, DPR RI Regulation Number 1 of 2020 on House Rules, DPR Regulation Number 2 of 2020 on Lawmaking, and Presidential Regulation Number 87 of 2014. This study uses the Normative Legal Research Method, with a statute approach. The research findings show that the DPR’s legislative authority includes the power to propose draft laws, to deliberate jointly with the President, and to enact draft laws into law. Although the DPR constitutionally holds the power to create laws, in practice, this authority is still exercised within the framework of the distribution of power, involving both the President and the Regional Representative Council (DPD). This article emphasizes that the DPR’s dominance in legislation has been reinforced after the amendments to the 1945 Constitution, yet its implementation still faces political and procedural dynamics that require strengthening of coordination mechanisms, public participation, and balance between state institutions to ensure the creation of democratic and accountable laws.